ADIKSI SMARTPHONE MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS SUMATERA UTARA ANGKATAN 2018 SELAMA PANDEMI COVID-19 - Rizky Mildsi, Adam; Effendy, Elmeida (Universitas Methodist Indonesia, 2022)
Background: Digital technology addiction includes internet addiction, social media addiction, smartphone addiction, online gaming addiction, and online gambling addiction. Someone who spends a lot of time using digital technology and internet-related activities will cause dependence on technology for social interaction, entertainment, and information resources. This will lead to increased mental disorders, emotional instability, and sleep disturbances. Since the COVID-19 pandemic began, many prevention and control strategies have been implemented by the Indonesian government to suppress the spread of this virus. One of the best ways to suppress the spread of this virus is to stay at home. This affects the daily activities of people around the world which leads them to use digital technology more often, such as the internet, social media, and smartphones Methods: This study aims to evaluate association between gender, age, and residence with smartphone addiction among students of the 2018 Faculty of Medicine, North Sumatra University during COVID-19 pandemic. The type of research used in this study is a analytic observational study with a cross-sectional design. The research sample was obtained using the large-sample method based on proportions with the research sample population being all students of the Medical Education Study Program, Faculty of Medicine, University of North Sumatra, 2018. The data was obtained online using a questionnaire Conclusion: Among 80 respondents there are 59 people experiencing smartphone addiction and there is no significant association between gender, age, and residence with smartphone addiction.